Cervical dystonia: about familial and sporadic cases in 88 patients - Carlos Henrique F. Camargo; Sarah Teixeira Camargos; Nilson Becker; Renato Puppi Munhoz; Salmo Raskin; Francisco Eduardo C. Cardoso; Hélio Afonso G. Teive (Arquivos de Neuro-Psiquiatria)
Cervical dystonia (CD) affects the musculature of the neck in a focal way or associated to other parts of the body. The aim of this study was to identify clinical differences between patients with dystonia patients without family history and with family history (sporadic). Eighty-eight patients with CD were recruited in a Movement Disorders Clinic between June of 2008 and June of 2009. Only patients with no etiological diagnosis were accepted for analysis. The age of onset of symptoms was later in patients with focal and segmental dystonia than in patients with generalized dystonia (p<0.001). The severity of symptoms was higher in patients with sporadic dystonia than in familial patients (p<0.01). Generalized cases were more severe in patients with a family history (p<0.01). Sporadic patients had higher levels of pain than familial cases (p<0.05). We expect soon to present the results of genetic analyzes of these patients.